Education amidst COVID-19 Disruption: Perceived Difficulty in Implementing Flexible Learning Strategies of Teacher Education Faculty Members in a State University - Lagat, Kevin T. (Philippine Social Science Journal, 2020)
This descriptive-correlational study described and analyzed the perceived difficulty in implementing Flexible Learning (FL) strategies of 60 teacher education faculty members of a state university in an eastern province in the Philippines. Moreover, this study investigated the correlation between the faculty members’ demographics and their perceived difficulty in implementing flexible learning strategies. Data were collected using a researcher-made questionnaire and analyzed using weighted mean, standard deviation, Spearman Rho Correlation, and Rank-Biserial Correlation. Results revealed that faculty members, in general, considered flexible learning strategies to be slightly difficult to implement. A significant relationship was also found between the faculty members’ generational age and their perceived difficulty in the Instructional Approach and Resources domain. The findings of this study suggest capacity building initiatives to address the identified difficult flexible learning strategies of the faculty members.